Gestalt Psychotherapy, Conflict and Resolution:: An Autoethnography - Talbot, Mike (European Journal for Qualitative Research in Psychotherapy, 2018)
This article is based around my experiences as a gestalt psychotherapist who became a full-time mediator. I describe how I have tried to deepen the theoretical underpinning of mediation with a gestalt dialogic-relational approach, and how I have applied my own skills and experience as a gestalt psychotherapist to being a mediator. Using autoethnography as the research method, I analyse aspects of myself and my motivations, and the relationships I have had with people within the mediation field. I conclude that mediation practice would indeed benefit from a greater knowledge of relational, especially gestalt, theory. I also comment on some of my experiences of trying to introduce this much more theory-rich approach, and on how it has been received by other mediation professionals.